The Use of Anthelmintics in the Treatmenlt of Ascariasis - Djauhar Ismail; Utomo Utomo; Sugeng Yuwono; Noerhayati S. (Indonesian Pediatric Society, 1976)
Ninety-seven children with Ascariasis were treated at randomly with Piperazine, Tetramisole, and Pyrantel pamoate in a single dose with cure rates of 59%, 62%, and 88%, respectively. In the children who were not cured, a reduction in egg count of nearly 80% was found in all three treatment groups. The results of this study showed that Pyrantel pamoate is the most effective of the three drugs.